THE RISE OF CHILD MARRIAGE IN PALU CITY - Susilawati, Susi; Ridwan, Ashar; Maddusila, Sitti Fatimah (Tadulako University, 2021)
Act Number 16 Year 2019 on Marriage stipulates that the minimum age for marriage for a person is 19 years for both men and women. Whereas the previous Act stipulated the age limit of marriage, 19 years for men and 16 years for women. This is considered very burdensome for some religious people who obey traditions and laws as well as other factors. Thus, child marriage in the period before the Marriage Act Amendment was already quite high and it is even higher afterward. This writing aims to determine and analyze how many applications for marriage dispensation after the Amendment of the Marriage Act at the Religious Court of Palu City, using empirical research methods. The results showed that there was a significant increase in applications for marriage dispensation in the Religious Court of Palu City after the amendment.